HUMAN CAPITAL MANAGEMENT SEBAGAI SUATU SISTEM YANG DIRANCANG UNTUK MENCIPTAKAN KEUNGGULAN KOMPETITIF YANG BERKELANJUTAN - Sulbahri Madjir (Fakultas Ekonomi Universitas Tridinanti Palembang, 2013)
Human Capital ManagementÃ‚Â argues that sustainable profit generated when a company provides products and services that meet customer needs better than competitors do. In other words, it will be achieved if the company has a competitive advantage. Efforts to maintain a competitive edge should be at all times so that the competency or corporate activity and superior rated best by customers compared to competitors, both in view of existing customers, and potential customers. Human capital management is a system to improve the performance of their important role in a company and a major impact on corporate competencies. The blueprint for creating a sustainable competitive advantage should focus on improving performance in implementing key role to enhance the core capabilities. The company creates sustainable competitive advantage through high-quality human resources and organizational capabilities through human capital. The four components that make up the human capital strategy, namely (1) the effective executive team, (2) Leaders who deliver results, (3) key position excellence, (4) Fleet Performance Work. If the performance of each component of the strategy is exellent, the organization will have a sustainable Competitive advantage. To perform the four components of the strategy the company needs to have (1) sufficient organizational capability to deliver the strategy, (2) The definition of success in business, (3) an integrated process improvement, (4) measurement and management disciplines.Ã‚Â Key Words : Human Capital Management, Competitive advantage